Listening well : bringing stories of hope to life - Morris, Heather (Screenwriter) (St. Martin's Press, 2022)
"From New York Times bestselling author Heather Morris comes the memoir of a life of listening to others. In Listening Well, Heather will explore her extraordinary talents as a listener-a skill she employed when she first met Lale Sokolov, the tattooist at Auschwitz-Birkenau and the inspiration for her bestselling novel. It was this ability that led Lale to entrust Heather with his story, which she told in her novel The Tattooist of Auschwitz and the bestselling follow up, Cilka's Journey. Now Heather shares the story behind her inspirational writing journey and the defining experiences of her life, including her profound friendship with Lale, and explores how she learned to really listen to the stories people told her-skills she believes we can all learn. "Stories are what connect us and remind us that hope is always possible."-Heather Morris"--